2011
DOI: 10.5301/ejo.5000003
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Ahmed Valve for Selected Cases of Refractory Glaucoma

Abstract: Flexible Ahmed glaucoma valve plate implant is a satisfactory method for controlling elevated IOP in cases of refractory glaucoma with success rate of 92.5% and lower incidence of immediate postoperative and implant-related complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…The Ahmed Baerveldt Comparison Study stated a rate of 19% [17], but Choo's study reported a value of only 2.63% [18]. Intraoperatively injecting the appropriate volume of viscoelastics to deepen the anterior chamber is crucial to reduce the rate of postoperative flat anterior chamber [19,20]. The anterior chamber did not exhibit recurrence of shallowing in these four cases after a single surgical intervention.…”
Section: Discussionmentioning
confidence: 87%
“…The Ahmed Baerveldt Comparison Study stated a rate of 19% [17], but Choo's study reported a value of only 2.63% [18]. Intraoperatively injecting the appropriate volume of viscoelastics to deepen the anterior chamber is crucial to reduce the rate of postoperative flat anterior chamber [19,20]. The anterior chamber did not exhibit recurrence of shallowing in these four cases after a single surgical intervention.…”
Section: Discussionmentioning
confidence: 87%
“…These results are similar to the results Ishida et al [21] reported: a 94.2% success rate with FP7 implant at 12 months. In 40 eyes from 40 patients with different types of refractory glaucoma, a 92.5% success rate was reported with both FP7 and FP8 after a follow-up period of 6 months [22]. Unfortunately, this study did not report separate success rates between FP7 and FP8 groups.…”
Section: Discussionmentioning
confidence: 92%
“…[11][12][13] Glaucoma drainage devices are also used to treat PCG. 14,15 The use of antimetabolites eg 5-fluorouracil and mitomycin C reduces scarring and increases the success rates. 16 Non-penetrating deep sclerectomy (NPDS) is another alternative where the surgeon elevates a partial thickness scleral flap and removes the external portion of Schlemm's canal together with the outer part of the trabecular meshwork including the juxtacanalicular tissue without full penetration inside the eye.…”
Section: Introductionmentioning
confidence: 99%